Forms of Address to Superior and Organizational Culture in Japan Creative Industry - Cece Sobarna, Elisa Carolina Marion,; Rumeser, Johannes A.A.; Ardiati, Riza Lupi (Opción, 2020)
The objective of this research is to identify the form of address used to superiors in companies, uniquely creative industry in Japan. This research is a preliminary study for a research that aims to prove the relationship between the use of language and organizational culture in a company. The method used was qualitative research by an in-depth interview with participating employees who work in Japan’s creative industry. The results show that the 2 (two) companies used "family name +san" to address superiors, and used "family name + professional ranking" to address president or shachou.